INTEGRASI SISTEM PENJUALAN MELALUI WEBSITE DAN APLIKASI MOBILE BERDASARKAN 7C’S FRAMEWORK (Studi: CV Alam Organik Makmur) - Lauwis, Lauw Melissa; Budiastuti2, Dyah; Rudy, Rudy (Bina Nusantara University, 2013)
The growth of sports nutrition supplement sales is associated with the role of a good system inside the company which implements a business supportive information technology. It is a system that is capable to integrate its sales system with finance and administration system, as well as other functional system that is accessible through website or mobile. The objective of this research is to identify and develop an integrated system feature based on 7C’s framework. By the end of this research, the deliverable is a fully functional integrated system using an android and web based mobile application. This system shall be capable to mitigate or solve company’s current issue and eventually lift the sales growth itself.